2020
DOI: 10.1136/gpsych-2020-100215
|View full text |Cite
|
Sign up to set email alerts
|

Burden of care in caregivers of patients with alcohol use disorder and schizophrenia and its association with anxiety, depression and quality of life

Abstract: BackgroundCaregivers play a pivotal role in providing care for mentally ill patients. Increase in caregiver burden can make them vulnerable to mental illness themselves.AimsWe assessed the severity of burden of care and its association with depression, anxiety and quality of life among caregivers of patients with alcohol use disorder (AUD) and schizophrenia.MethodsThis was an observational, cross-sectional, single-centred study of 50 consecutive caregivers of patients with AUD and schizophrenia. Participants w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 21 publications
2
34
0
Order By: Relevance
“…One study found that high caregiver burden often occurs with comorbid anxiety and depression. 10 Another study with a longitudinal design also reported that caregivers who experienced many difficulties associated with care were likely to feel high care burden. 11 Since this study had a cross-sectional design, causal inferences and the direction of causality cannot be determined.…”
Section: Discussionmentioning
confidence: 99%
“…One study found that high caregiver burden often occurs with comorbid anxiety and depression. 10 Another study with a longitudinal design also reported that caregivers who experienced many difficulties associated with care were likely to feel high care burden. 11 Since this study had a cross-sectional design, causal inferences and the direction of causality cannot be determined.…”
Section: Discussionmentioning
confidence: 99%
“…15,16,32,32,33 Studies have shown that the burden of disease may be associated with symptoms of anxiety and depression. 29,35 In a study conducted by Vadher et al, 29 the caregivers of patients with schizophrenia were more likely to have depression, anxiety, and poor QoL when the burden of care was higher. The caregiver's burden of care can also be predicted by anxiety and environmental QoL, possibly because the burden of caring reduces a caregiver's ability to cope with illness.…”
Section: Discussionmentioning
confidence: 99%
“…These prevalent and debilitating mental disorders can seriously impact daily life, including school performance, work productivity, family and friend interpersonal relationships, and community participation 4 5. Many studies also show strong relationships between these disorders and physical health problems such as tuberculosis, cardiovascular disease, disturbed concentration, sleep disorder and appetite 6–9. Individuals from all countries—young and old, rich and poor—suffer from these conditions.…”
Section: Introductionmentioning
confidence: 99%
“… 4 5 Many studies also show strong relationships between these disorders and physical health problems such as tuberculosis, cardiovascular disease, disturbed concentration, sleep disorder and appetite. 6–9 Individuals from all countries—young and old, rich and poor—suffer from these conditions. Previous research findings indicate that women, persons with higher education, and urban-dwelling individuals are more likely to have depression and anxiety than men, illiterate individuals, and villagers living in rural communities.…”
Section: Introductionmentioning
confidence: 99%